2018
DOI: 10.1148/radiol.2018172600
|View full text |Cite
|
Sign up to set email alerts
|

US Molecular Imaging of Acute Ileitis: Anti-Inflammatory Treatment Response Monitored with Targeted Microbubbles in a Preclinical Model

Abstract: Purpose To evaluate whether dual-selectin-targeted US molecular imaging allows longitudinal monitoring of anti-inflammatory treatment effects in an acute terminal ileitis model in swine. Materials and Methods The Institutional Animal Care and Use Committee approved all animal studies. Fourteen swine with chemically induced acute terminal ileitis (day 0) were randomized into the following groups: (a) an anti-inflammatory treatment group (n = 8; meloxicam, 0.25 mg per kilogram of body weight; prednisone, 0.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Once intravenously injected, MB Selectin remains attached to P- and E-selectin expressed in the inflamed vascular wall for an extended period of time, during which multiple bowel segments can be imaged. Dual-selectin targeted USMI has been validated in murine and swine models of IBD for assessing different degrees of inflammation and monitoring treatment outcomes using histology and immunofluorescence staining as gold standards 15-18. In these small and large animal models of IBD, acute inflammation has been chemically induced using [2,4,6-trinitrobenzenesulfonic acid (TNBS)].…”
Section: Introductionmentioning
confidence: 99%
“…Once intravenously injected, MB Selectin remains attached to P- and E-selectin expressed in the inflamed vascular wall for an extended period of time, during which multiple bowel segments can be imaged. Dual-selectin targeted USMI has been validated in murine and swine models of IBD for assessing different degrees of inflammation and monitoring treatment outcomes using histology and immunofluorescence staining as gold standards 15-18. In these small and large animal models of IBD, acute inflammation has been chemically induced using [2,4,6-trinitrobenzenesulfonic acid (TNBS)].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments in colitis induced mice showed that molecular US assessment of IBD excellently correlated with 18 FDG-PET (positron emission tomography) and histological examination [ 130 ]. Further studies in swine demonstrated that dual-targeted UCA have the potential for clinical translation [ 131 , 132 ]. Wang and co-workers showed that, one hour after inflammation induction by exposing ileum to 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) and ethanol, a significant increase in CEUS signal occurred [ 131 ].…”
Section: Targeted Contrast Agentsmentioning
confidence: 99%
“…The US signal changed in line with the increased selectin expression and further increased with the progression of the inflammation. Moreover, P- and E-selectin-targeted MB also proved promising for long-term monitoring of anti-inflammatory IBD treatment in swine [ 132 ]. The combination treatment of prednisone and meloxicam reduced inflammation and downregulated selectin expression in the inflamed vasculature in the bowel.…”
Section: Targeted Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next rational question was whether molecularly targeted US imaging can also be used for therapy monitoring. This question is addressed by Wang et al in this issue of Radiology (7). In this study, acute ileitis was induced in pigs by injecting a mixture of 2,4,6-trinitrobenzene sulfonic acid in ethanol into the distal ileal lumen.…”
mentioning
confidence: 93%